Interoperability, blockchain and innovation: Open Music Initiative’s case for a networked phonographic industry - Paula Filho, Gilberto Paschoal de (2019)
As recorded music industry begins to regain financial traction in a digitized market, it still faces the dim reality of high transaction costs, low levels of transparency and asymmetric information contexts. Artists, rights holders and entrepreneurs alike are constantly dealing with the difficulties in making business based on creative works. In the academic scene we still face a shortage of case studies on the topic, with most of the research being focused on theoretical analysis or technical experiments. This paper assays Open Music Initiative (a non-profit that involves academic institutions and major music and media organizations) as a comprehensive effort that can establish a cross industry standardization of technical protocols and metadata in order to create interoperability, fostering technological innovation and new businesses.